The Noteworthy Case: Atypical Palatal Ulcer Which is Progressivelly Develop to Oral Squamous Cell Carcinoma in Diabetic Elderly - Prayudha, Satrya Ayu E.; Chrismawaty, B. Esti; Agustina, Dewi; Subagyo, Goeno (The Indonesian Journal of Dental Research)
Background: Oral ulcers are commonly painful lesions that are associated with numerous etiologies. Palatal ulcer could be referred as atypical oral ulcer due to unusual site predilection. The correct differential diagnosis is necessary to establish the appropriate treatment, with regards to all possible causes. Purposes: This report was intended to explain Oral Squamous Cell Carcinoma [OSCC] which is presented as atypical palatal ulcer resembling Necrotizing Sialometaplasia [NS]. Case and management: A 65 year old male, edentulous with history of uncontrolled type 2 Diabetes mellitus and experienced a gradually enlarging palatal ulcer. According to the patient, a fish bone pricked his hard palate just before the complaint. There was no lymphadenopathy, and intraoral examination revealed a solitary shallow ulcer on the right side of hard palate, covered by white pseudomembranous layer without erythematous halo. The margin of the ulcer was distinctive without induration. A month later, the lesion was progressively painful and interfere the oral function. The differential diagnoses were traumatic ulcer suspected to Eosinophilic Ulcer, Necrotizing Sialometaplasia [NS], and OSCC. Treatment plans included palliative measures and medical consultation regarding the need of biopsy. The biopsy was performed two months later. At that time, the ulcers were enlarged with indurated margin and necrotic center. A biopsy confirmed the diagnosis as OSCC with moderate differentiation. For proper treatment, the patient was referred to Oncology Department, Sardjito General Hospital. Conclusion: An atypical persistent solitary oral ulcer, especially in elderly, should prompt urgent investigation, since an oral malignancy must be foremost on the differential diagnoses list. This case report showed a progressively development of OSCC, even without preceding premalignant lesion. It is the dentists responsibility to identify any suspicion of oral premalignancy, so that proper referral can be performed earlier for reducing the mortality.